Teaching Note—Beyond the Binary: Addressing Cisnormativity in the Social Work Classroom. (2nd January 2020) - Shelton, Jama; Dodd, SJ
ABSTRACT: Social work educators are responsible for ensuring their students are equipped to rise against social injustice. Therefore, the marginalization of transgender, genderqueer, and nonbinary people and communities must be addressed in the social work classroom. Contextualizing the social work classroom within cisnormativity, this article reports on the ways social work classrooms may perpetuate the marginalization of transgender, genderqueer, and nonbinary populations. Practical recommendations for recognizing cisnormative practices and creating transgender-inclusive classrooms are provided.